234 An Evaluation of Two Frailty Intervention Therapy Team's (FITT) in the Emergency Department Pilot Services. (16th September 2019) - Walsh, Ciara; McCullagh, Ruth; O'Connor, Kieran; Higgans, Anna; O'Callaghan, Donal; Timmons, Suzanne
Abstract: Background: Frailty is an important marker of adverse outcomes for older people accessing the Emergency Department (ED). Older patients with frailty have a higher attendance rate to the ED, spend longer in the ED and have a higher rate of admission (HSE, 2017). Frailty Intervention Therapy Teams (FITT) are designed to screen and assess this population in the ED setting, with the aim of early assessment to help decrease length of stay or avoid admission. Two different FIT Teams have recently been formed within the Cork-Kerry region. The aim of this study was to evaluate staff's experience of these teams. Methods: This was a mixed methods study. Structured surveys were developed to collect qualitative and quantitative data. The surveys were constructed using themes listed by Proctor et al., (2011) around implementation and service outcomes. Ward and ED staff were provided with paper surveys within the hospital setting and community staff were surveyed via post. Quantitative survey data was analysed using descriptive statistics and qualitative data was analysed with thematic content analysis. Results: Data from 117 surveys was included for analysis (response rate 49%). Results showed that the majority of staff (89%) reported ED was a suitable setting for the FITT, with 85% reporting the information collected by the FITT impacted their involvement. Other themes emerging from staff's experience included timeliness, safety and comprehensive assessment. Conclusion: Overall, staff reported the FITT provided a timely service that assisted with decision making and planning. This involved earlier comprehensive assessment, prompt identification of issues which lead to decreased workload for ward staff. It also created an increased volume of referrals to community and ward staff received in a timelier manner.